Structure-property correlation of halogen substituted benzothiazole crystals - Thekkeppat, Nipun P.; Singla, Labhini; Tothadi, Srinu; Das, Priyadip; Choudhury, Angshuman Roy; Ghosh, Soumyajit (Journal of Molecular Structure, 2021)
We have synthesized 3 benzothiazole crystals (1-3) based on existing knowledge of combining flexibility and optical properties towards achieving applications for flexible optoelectronics. However, one crystal was found to be elastically bendable and was found to comply necessary packing features for elasticity. Other two crystals do not obey packing features for elasticity hence they are brittle in nature. Further, Hirshfeld analysis illustrates that elastic crystal 1 possess more number of weak and dispersive interactions compared to other crystals. These interactions were instrumental in invoking elasticity. Moreover, crystals 1-3 were found to be fluorescent as well at specific excitation wavelengths. Therefore, among these crystals, particularly crystal 1 is considered as more promising candidate for flexible optoelectronics. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Benzothiazole crystals; Elasticity; Halogen bond; mechanical properties

Simultaneously mechanically flexible, photobending, and acidochromic cyanostilbene molecular crystals - Parthasarathy, Thiyagaraj; Mishra, Manish Kumar; Bhattacharya, Biswajit; Emmerling, Franziska; Ghosh, Soumyajit (Crystal Growth & Design, 2024)
Molecular crystals that respond to multiple stimuli are gaining significant attention for their potential in smart materials like actuators and sensors. However, imparting multiple stimuli-responsive properties to a single crystal remains a major challenge. Herein, we report two cyanostilbene derivative-based crystals 1 and 2, with various responses to stimuli such as mechanical stress, light, acid vapors, etc. Both crystals 1 and 2 demonstrated mechanical flexibility and reversible acidochromism. Additionally, crystal 1 also exhibited light-induced photobending, which is ascribed to Z to E photoisomerization. Detailed structure-property correlation was established to unravel distinct mechanical responses. The development of these multitasking crystals may find applications in multitasking actuators, anticounterfeiting materials, and more.